University of bologna: history, traditions, nowadays - Tkachenko Marharyta (Borys Grinchenko Kyiv Metropolitan University, 2015)
The objective of the national higher education in Ukraine is to reformation and adaption according to international agreements on creation of common European educational space. The process of formation of the European education area is called Bologna. Despite many years of educational work, many course offerings for undergraduate and graduate students, even specialists remain the main ideas of the Bologna process unattended. Clarification of regularities of appearance and development of the name "Bologna process" through understanding the history and traditions of the University of Bologna, will give the necessary explanations. The paper summarizes the history of the University of Bologna. Recreated the traditions in the organizational principles of University education in Italy during the time of foundation of the first universities. The author explains the difference between the principles of the founding of the University of Bologna and University of Paris, which were founded one of the first and which began a tradition of differences between the Southern and Northern universities. The article noted the precedent of the student government, what embedded in the institutional framework of the University of Bologna. The author defines the mission of the University of Bologna in educational-political movement that became known as the Bologna process. The tradition of higher education, founded in the University of Bologna, has continued until now. A wide selection of training programs, quality of education responding to the world standards, and student self-government.